AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SURUHAN (Peperomia pellucida L. Kunth) TERHADAP BAKTERI Staphylococcus aureus - Isna Jati Asiyah; Destik Wulandari (Fakultas Farmasi Universitas Setia Budi, 2019)
ABSTRACT Staphylococcus aureus causes infectious diseases include breast inflammation (mastitis), endocarditis, respiratory tract infections, and infections of the skin. Drug from natural resources need because β-lactam group antibiotic activity had been resistance to S. aureus. The herb plants (Peperomia pellucida L. Kunth) has active tannins and flavonoids act as antimicrobials. This research aims to determine antibacterial activity of leaf extract (Peperomia pellucida L. Kunth) against S. aureus. The leaf leaves were extracted by maceration using 70% ethanol solution, then an antibacterial test was carried out using the dilution method to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Extracts was made in 5 series concentration: 100%, 80%, 60%, 40%, and 20%. The results showed MIC value could not be determined because the mixture between the leaf extract and S. aureus bacteria was very cloudy. MBC obtained from the antibacterial activity test of leaf extract on S. aureus bacteria was 40%.